Identifikasi Struktur Kerak Di Bawah Permukaan Jawa Timur Berdasarkan Hasil Tomografi Seismik Menggunakan Model Kecepatan Gelombang P Dan Gelombang S - Uli Ulfa; Rahmawati Fitrianingtyas; Yohana Noradika Maharani; Adhi Wibowo (Jurnal Teori dan Aplikasi Fisika, 2023)
Tectonic conditions that are vulnerable to earthquakes have become a trigger for researchers to conduct studies on subsurface conditions in East Java. A seismic tomographic study based on the P-wave and S-wave velocity models was applied to identify crustal structures in East Java. The research data totaled 3,893 earthquake events and 28 stations from the Meteorology, Climatology and Geophysics Agency (BMKG) in the 2009-2017 period covering coordinates 5oSL- 11oSL and 110o - 115o EL. The modeling results in this study are expressed in velocity perturbations against the ak135 one-dimensional reference velocity between -5% to 5%. The results of this study indicate that in the central of East Java, there is a negative velocity anomaly which is identified as a sedimentary layer that fills the basin in the Kendeng Zone and volcaniclastic deposits in the Southern Mountains Zone to a depth of 5 km. The dominant negative velocity anomaly in southern East Java is associated with the presence of intrusive and bedrock in the Southern Mountain Zone. The transition zone between the crust and upper mantle in East Java is observed at a depth of 35 km below the surface.